Language institutions and language criticism in European perspective - Radtke, Edgar; Große, Sybille; Felder, Ekkehard (Handbuch europäische Sprachkritik online, 2019)
This article examines state institutions with a political mandate to standardise and to regulate the standardisation of a national language, along with non-state-mandated associations (e. g. linguistic societies, language or cultural associations) that have dedicated themselves to this cause. Against this backdrop, the highly prestigious language academies in Italy, France and Croatia, which have long been active in the establishment of standards, are compared with the linguistic-political activities being pursued in countries where there are no such institutions. All institutions and associations, regardless of their state or social ties, have one thing in common: they all want, as regards self-attribution, they all want to contribute to their individual societies through the cultivation of their languages.
Gesehen am 26.06.2020